2022
DOI: 10.1017/s1049023x22000310
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Portable Oxygen Concentrators in Low-Resource Settings: A Systematic Review

Abstract: Introduction: Portable oxygen concentrators (POCs) are medical devices that use physical means to separate oxygen from the atmosphere to produce concentrated, medical-grade gas. Providing oxygen to low-resources environments, such as austere locations, military combat zones, rural Emergency Medical Services (EMS), and during disasters, becomes expensive and logistically intensive. Recent advances in separation technology have promoted the development of POC systems ruggedized for austere use. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The use of home ventilatory support devices has increased since the COVID-19 pandemic. [17][18][19] Studies have shown that LTOT increases survival by improving lung function in patients with chronic respiratory failure. LTOT also improves the quality of life and reduces the frequency of recurrence and hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of home ventilatory support devices has increased since the COVID-19 pandemic. [17][18][19] Studies have shown that LTOT increases survival by improving lung function in patients with chronic respiratory failure. LTOT also improves the quality of life and reduces the frequency of recurrence and hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Ismail et al published a review article on the source and distribution of medical oxygen in January 2022, focusing on the aspect of COVID-19 [10]. Nowadly et al have issued the only systematic review on this issue [11], where they assessed the use of portable oxygen concentrators (POC) in low-resource settings, according to the Preferred Reporting Items for Systematic review and Meta-Analysis Protocols (PRISMA-P) [12]. Later in April, Jha et al published a concise review on the life cycle of medical oxygen, focusing on the crisis faced by India during the second wave of COVID-19 [13].…”
Section: Introductionmentioning
confidence: 99%